IDENTIFIKASI PELAKSANAAN PROGRAM PEMBINAAN KESEHATAN LANSIA DI PANTI SOSIAL TRESNA WERDHA KHUSNUL KHOTIMAH PEKANBARU - Ferguson " "; Ari Pristiana Dewi; Safri " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Elderly is the final stages of the development cycle on the life of a human being need mentoring programme that includes an effort promotif, preventive, curative, and rehabilitative programmes. The purpose of this research is to know the characteristics of the elderly health coaching program implementation in Khusnul Khotimah Nursing Home Social Services Unit. The method of this research is quantitative descriptive with cross sectional design. This research was conducted in Khusnul Khotimah Nursing Home Social Services Unit of Pekanbaru. Sample data retrieval method is the total sampling by the number of respondents 74, 60 elderly people, 6 health workers and 8 elderly pramu. Measuring instrument used was a questionnaire. Results of the study showed that most respondents do elderly health coaching programs efforts promotif most of the elderly who do janitorial maintenance health and self contained 60 elderly (100%), a preventive known result that on the elderly there are 57 elderly (95%) who perform health checks on a regular basis, there are 54 elderly elderly curative (95%) of doing health services such as cholesterol checks, IMT, and blood sugar and rehabilitative programmes there are 53 (88%) elderly who obtain information of knowledge about AIDS (spectacles and hearing) in Khusnul Khotimah Nursing Home Social Services Unit of Pekanbaru. The results of this research are expected to utilize the elderly health program implementation efforts curative, health workers and pramulansia to improve preventative and promotif degrees of health elderly in Khusnul Khotimah Nursing Home Social Services Unit. Keywords: Characteristics of elderly health coaching program implementation